Mineral absorption is an enriched pathway in a brain region of restless legs syndrome patients with reduced MEIS1 expression - Sarayloo, Faezeh; Dionne-Laporte, Alexandre; Catoire, Helene; Rochefort, Daniel; Houle, Gabrielle; Ross, Jay P.; Akçimen, Fulya; Barros Oliveira, Rachel De; Turecki, Gustavo; Dion, Patrick A.; Rouleau, Guy A. (PloS one, 2019)
Restless legs syndrome is a common complex disorder with different genetic and environmental risk factors. Here we used human cell lines to conduct an RNA-Seq study and observed how the gene showing the most significant association with RLS, MEIS1, acts as a regulator of the expression of many other genes. Some of the genes affected by its expression level are linked to pathways previously reported to be associated with RLS. We found that in cells where MEIS1 expression was either increased or prevented, mineral absorption is the principal dysregulated pathway. The mineral absorption pathway genes, HMOX1 and VDR are involved in iron metabolism and response to vitamin D, respectively. This shows a strong functional link to the known RLS pathways. We observed the same enrichment of the mineral absorption pathway in postmortem brain tissues of RLS patients showing a reduced expression of MEIS1. The expression of genes encoding metallothioneins (MTs) was observed to be dysregulated across the RNA-Seq datasets generated from both human cells and tissues. MTs are highly relevant to RLS as they bind intracellular metals, protect against oxidative stress and interact with ferritins which manage iron level in the central nervous system. Overall, our study suggests that in a subset of RLS patients, the contribution of MEIS1 appears to be associated to its downstream regulation of genes that are more directly involved in pathways that are relevant to RLS. While MTs have been implicated in the pathogenesis of neurodegenerative diseases such as Parkinson's diseases, this is a first report to propose that they have a role in RLS.